Análise de indicadores para execução de inspeção predial regular obrigatória e diretrizes para o corpo técnico - Vervloet, Suzanne (2018)
The building inspection is an indispensable tool for the technical monitoring of the conservation state, use and maintenance of buildings. Since 2001, several brazilian cities turned into mandatory, the regular building inspection, alerted by the occurence of acidentes which causes were related to the lackness of conservation of buildings. To supply the guidelines to the inspector professionals, the legislation in general recomend the attendance to the technical standards in force. The Norma de Inspeção Predial Nacional (IBAPE, 2012) represents an advance regarding the technical recomendations of the specific activity of building inspection, since the national regulator agency – ABNT – doesn’t have a published standard about this subject. However, some of the guidelines of the Norma de Inspeção do IBAPE require refinement and standardization in order to minimize the variability of results of the inspection reports. In this context, the aim of this research is to identify the deficiencies of legislation and normatization in force regarding to the execution and register of regular building inspection by the technical body and propose resolutive guidelines. A wide bibliographic revision, in varied and disperse sources of information, supports itself in a consistent methodology of collect, storage and evaluation of data. The creation of a database with numeric classification and dynamic feeding enables this organization. Due to the particularities of Municipal Law, the City of Vitória, ES is selected as case study. Conclusively, five results are presented: (1) Verification list for the structural system, as example of the detailing level suggested in the survey directions; (2) The GUT-SC method of anomalies and failures priorization, with well defined criteria of risk analysis, besides cost range as auxiliary tool; (3) The metodology of execution of building inspection, since hiring to delivery of the Building Inspection Report (LIP); (4) Model for the Building Inspection Report; (5) Orientative guide of costs related to the elaboration of LIP. The guidelines presented in the results compose a complete and detailed metodology of execution and register of building inspection. Once unified its application, they allow the standardization of the activity and its costs, with consequent homogenization of Building Inspection Reports, in benefit of the professionals, managers of buildings and supervisory organ.